Pengaruh kecepatan gerak torch pemanas pada proses automatic flame hardening terhadap nilai kekerasan dan kekuatan tarik baja karbon medium - Andi Purwanto; Teguh Triyono; Sukmaji Indro Cahyono (Mekanika: Majalah Ilmiah Mekanika, 2018)
Steel material was widely used and obtained in the industry and automotive application. The hardness of the surface area and the ductile of the core were produced by using heat treatment, in this case, automatic flame hardening method was used. The heat treatment process was done in order to increase the surface temperature by using a carburizing flame and then the cooling process by using water cooling medium continously followed. The aim of this research was to identify the effect the heating torch velocity on the surface hardness and the tensile strength of the medium carbon steel using the automatic flame hardening process. Some variations were used in this research were heating torch velocities at 10 mm/min, 20 mm/min, 30 mm/min, and 40 mm/min. The results shows that the heating torch velocity at speed 10 mm/min was the most optimal parameter. The maximum hardness of the surface area is reached 398.9 VHN, while the highest tensile strength was 647.3 MPa and the perlit-ferrit phase was also formed. By these results, the hard properties on the surface area and the ductile properties in the middle area of the specimen could be obtained.